RESULTS OF THE ENUMERATION OF COSTAS ARRAYS OF ORDER 29 - WALSH, JOHN (My University, 2011)
The results of the enumeration of Costas arrays of order 29 are presented: except for 16 arrays out of a total 164, all other arrays found are accounted for by the Golomb and Welch construction methods. These 16 arrays, however, cannot be considered to be new, as they were discovered in the past through a semi-empirical technique. The enumeration was performed on several computer clusters and required the equivalent of 366.55 years of single CPU time.
PUBLISHED
Keywords: Mathematics; Costas arrays; enumeration; order 29; Golomb method; Welch method